Factors Associated With Work Fatigue Among Tank Truck Crew at Fuel Terminal Biak - Rahmi Apriani; Sarah Handayani (INDOGENIUS, 2026)
Background & Objective: Work-related fatigue remains a significant concern in occupational health and safety, particularly in roles that demand high levels of physical exertion, such as fuel transportation. This study seeks to compare factors contributing to fatigue among fuel truck operators at Fuel Terminal Biak with findings from two prior investigations: one involving waste collectors in Kendari, and another examining lifting equipment operators at PT Pelindo IV Kendari Branch. The analysis focuses on three primary variables: workload, employment duration (tenure), and working hours or shift patterns. Method: All three studies applied a quantitative method with a cross-sectional design and utilized chi-square tests for statistical analysis. Result: The findings suggest that workload and job tenure consistently exhibit a significant correlation with fatigue across all occupational groups examined. In contrast, the impact of work hours appears inconsistent, with notable influence from contextual factors such as sleep quality and the implementation of night shifts. Conclusion: These results highlight the need for customized work scheduling and comprehensive fatigue management. The study underscores the importance of targeted interventions by employers and policymakers through strategies such as balanced workload distribution, structured rest periods, and ergonomic support. Such efforts are particularly critical in physically demanding and high-risk industries like fuel distribution, where fatigue poses direct threats to safety and operational efficiency.